Analysis of Alternative Splicing and Alternative Polyadenylation in Populus alba var. pyramidalis by Single-Molecular Long-Read Sequencing - Hu, Hongyin; Yang, Wenlu; Zheng, Zeyu; Niu, Zhimin; Yang, Yongzhi; Wan, Dongshi; Liu, Jianquan; Ma, Tao (Frontiers in Genetics, 2020)
Poplars are worldwidely cultivated with ecologically and economically important value. Populus alba var. pyramidalis (=P. bolleana) is a main tree of the farmland shelter-belt system in the arid region of Northwest China due to its rapid growth, erect stems and high biomass production. However, the full-length mRNA sequences and complete structure of Populus alba var. pyramidalis remain unclear. In this study, using single-molecular real-time (SMRT) and next-generation high-throughput sequencing (NGS) platform, we sequenced transcripts from leaf, root, xylem and phloem of Populus alba var. pyramidalis, to obtain the full-length mRNA transcripts and annotate the complete structure. In total, 86,327 mapped full-length non-chimeric (FLNC) reads were identified, with 705 previously unannotated loci and 3,410 lncRNAs and 174 fusion genes found. Alternative spicing (AS) events were detected in 7,536 genes, of which 4,652 genes had multiple AS events. A total of 10,213 alternative polyadenylation (APA) sites were identified, with two or more APA sites observed in 2,212 genes. Our transcriptome data provided the full-length sequences and gene isoforms of transcripts for Populus alba var. pyramidalis, which will be helpful in improving our understanding for the genome annotation and gene structures of Populus alba var. pyramidalis.